Human stress level computation using multiple physiological signals-based on fusion technique through dynamic bayesian network - Karthikeyan Palanisamy (School of Mechatronic Engineering, University Malaysia Perlis, 2014)
This study investigates to improve the stress levels computation and its reliability using multiple physiological signals. In which, stress inducement, physiological signal acquisition, preprocessing, feature extraction, classification, optimization of features from multiple physiological signals, significant feature estimation, decision boundary optimization, and fusion are the major process.